Perception of Russian employees' culture by Western managers of Western subsidiaries in Russia. Issue 2 (9th July 2018) - Valitova, Aysylu; Besson, Dominique
Abstract : Purpose: The purpose of this paper is to analyze perception of Russian national culture by Western managers in Western subsidiaries in Russia. Design/methodology/approach: Interpretivist analysis of narratives have been collected by the authors by interviewing several Western managers in Russian subsidiaries, based on concepts of E.T. Hall. Findings: We globally found more examples of high context than low context, but also of "hybrid context, " as well as more examples of polychrony than monochrony, and a mixture of polychrony and monochrony, the authors call "hybridchronie." They show implications of socio-economic change in society, organizational structure and work hierarchical relationship, generation effect and importance of clans. Research limitations/implications: Limits of cultural analysis. Use of interviews (narratives) then bias of perception. Current changes in Russian society. Differences between generations in Russia and multi-ethnicity of Russia. Practical implications: Danger of stereotypes in management. Implications for management. Social implications: Danger of stereotypes in perceptions and social life. Originality/value: Qualitative, interpretivist approach based on in-depth interviews.